Effect of the degree of hydrolysis and polymerisation on the melting process of thermoplastic poly(vinyl alcohol). (21st April 2018) - Luo, Yunying; Wang, Feng; Xu, Huan; Zhu, Hailin; Guo, Yuhai
ABSTRACT: In this work, the thermoplastic poly(vinyl alcohol) (TPVA) blend films were efficiently prepared using pure poly(vinyl alcohol) (PVA) and caprolactam–MgCl2 · 6H2 O via the aqueous method on the condition of achieving the melting process of PVA. The effect of the degree of polymerisation (DP) and hydrolysis (DH) of PVA on plasticisation was studied using Fourier transform infrared spectroscopy (FT-IR), X-ray diffraction, differential scanning calorimeter, and thermo gravimetric analysis. The plasticising effect increases initially and then decreases with the increase of DP owing to the destruction of hydrogen bonding and the decrease in regularity in PVA. The plasticising effect increases with the increase in DH, because the plasticiser weakens the hydrogen bonding of intro-intra molecular in PVA, which is confirmed by the shift of the –OH characteristic peak of FT-IR spectra. The thermal processing windows increase owing to the coordination effect between hydrogen bonding and crystallinity. TPVA-1799 had the largest thermal processing window (120°C) and the molten filament was extruded, which were both significant for melt spinning. GRAPHICAL ABSTRACT: